Relevansi Nilai-Nilai Universal Kemanusiaan dalam PAI: Respons terhadap Tantangan Intoleransi dan Krisi Moral - Ade Ramli Hidayat; Ilman Nafi’a; Hajam Hajam; Anam Khoirul Rozak; Meiza Fajar Akbar (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This study is motivated by the increasing challenges of diversity in the global era, such as intolerance, radicalism, and humanitarian crises, which reveal a gap between the universal values of Islam, namely Karāmah al-Insān and Rahmatan lil‘Ālamīn, and the social practices of some communities, including in the context of Islamic Religious Education (IRE). To address these issues, this study uses a qualitative approach based on literature review through conceptual analysis, literature synthesis, and content analysis of recent scientific references discussing human values, religious moderation, and the reconstruction of IRE pedagogy. The results of the study show that transformative PAI can only be realized through a paradigm shift from a normative-doctrinal approach to a humanistic-transformative model that is dialogical, contextual, digitally literate, and action-based, with teachers as uswah ḥasanah and agents of change. This study confirms that the integration of the values of Karāmah al-Insān and Rahmatan lil 'Ālamīn into case-based curriculum and learning methodologies, reflective dialogue, digital literacy, and service learning can strengthen the humanistic orientation of PAI and serve as an effective strategy in countering narratives of extremism and fostering social piety oriented towards Maqāṣid al-Syarī‘ah..